Approximation of copositive programming via linear programming using second order sum of square decomposition - Thanasak Mouktonglang (2018)
In this paper, we improve the previously known result of approximating the cone of copositive matrices. We approximate the cone of copositive matrices by a set of linear matrices inequalities using the second order sum of square decomposition. Hence, a copositive programming can be approximated more accurately by a linear programming.